Attention deficits revealed by passive auditory change detection for pure tones and lexical tones in ADHD children - Yang, Ming-Tao; Hsu, Chun-Hsien; Yeh, Pei-Wen; Lee, Wang-Tso; Liang, Jao-Shwann; Fu, Wen-Mei; Lee, Chia-Ying (Frontiers in Human Neuroscience, 2015)
Inattention has been a major problem in children with attention deficit/hyperactivity disorder (ADHD), accounting for their behavioral and cognitive dysfunctions. However, there are at least three processing steps underlying attentional control for auditory change detection, namely pre-attentive change detection, involuntary attention orienting, and attention reorienting for further evaluation. This study aimed to examine whether children with ADHD would show deficits in any of these subcomponents by using mismatch negativity (MMN), P3a, and late discriminative negativity (LDN) as event-related potential (ERP) markers, under the passive auditory oddball paradigm. Two types of stimuli - pure tones and Mandarin lexical tones - were used to examine if the deficits were general across linguistic and non-linguistic domains. Participants included 15 native Mandarin-speaking children with ADHD and 16 age-matched controls (across groups, age ranged between 6 and 15 years). Two passive auditory oddball paradigms (lexical tones and pure tones) were applied. Pure tone paradigm included standard stimuli (1000 Hz, 80%) and two deviant stimuli (1015 Hz and 1090 Hz, 10% each). The Mandarin lexical tone paradigm’s standard stimuli was /yi3/ (80%) and two deviant stimuli were /yi1/ and /yi2/ (10% each). The results showed no MMN difference, but did show attenuated P3a and enhanced LDN to the large deviants for both pure and lexical tone changes in the ADHD group. Correlation analysis showed that children with higher ADHD tendency, as indexed by parents’ and teachers’ rating on ADHD symptoms, showed less positive P3a amplitudes when responding to large lexical tone deviants. Thus, children with ADHD showed impaired auditory change detection for both pure tones and lexical tones in both involuntary attention switching, and attention reorienting for further evaluation. These ERP markers may therefore be used for evaluation of anti-ADHD drugs that aim to alleviate these dysfunctions.